2012
DOI: 10.21273/hortsci.47.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Yields and Soil Quality under Transitional Organic High Tunnel Tomatoes

Abstract: Interest in unheated plastic film-covered high tunnels to extend the growing season of high-value fruits and vegetables is growing rapidly, but sustainable soil management in intensively managed high tunnels is challenging. Yields, fruit quality, and soil quality in transition organic and conventional tomato were measured over the course of three growing seasons. Nitrogen (N) was applied at the rate of 112, 168, and 224 kg total N/ha in the form of chicken manure compost to the organic treatments and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…The four tunnels were 12.8 m long and 4.3 m wide and were built with polyvinyl chloride hoops covered with a single layer of 6-mil greenhouse plastic (Black et al, 2008a). Two of the tunnels were managed organically and the others by conventional approaches, which were a continuation of a previous study and to facilitate future studies (Reeve and Drost, 2012). The organic tunnels were fertilized with composted chicken manure to provide 150 kg nitrogen (N)/ha.…”
Section: Methodsmentioning
confidence: 99%
“…The four tunnels were 12.8 m long and 4.3 m wide and were built with polyvinyl chloride hoops covered with a single layer of 6-mil greenhouse plastic (Black et al, 2008a). Two of the tunnels were managed organically and the others by conventional approaches, which were a continuation of a previous study and to facilitate future studies (Reeve and Drost, 2012). The organic tunnels were fertilized with composted chicken manure to provide 150 kg nitrogen (N)/ha.…”
Section: Methodsmentioning
confidence: 99%
“…For example, imbalanced ratios between N, P, and K (42:11:47) were observed for tomato as compared with the crop demand (37:6:57) (Voogt et al 2011). Similarly, soil P accumulation was observed in high-tunnel tomatoes (Reeve and Drost 2012) as well as in other organic vegetables (Nachimuthu et al 2012). Consequently, excess soil P resulting from consecutive years of manure and compost amendments causes some organic growers to have to limit or eliminate the P supply on their farm.…”
Section: B Nutrient Budgetingmentioning
confidence: 99%
“…For horticultural crops, one way to alleviate the likely effects of climate change, such as water shortages, extreme temperature fluctuations, greater frequency of droughts and floods, exposure to air pollutants, and pest pressure, is the use of high tunnels and greenhouses. During the last decade, a considerable number of studies showed the benefits for growers, in terms of plant health, productivity, and quality, of using greenhouses (van Kooten et al 2008) and high tunnels for conventional as well as organic crops (Knewtson et al 2010;Bordeleau et al 2011;Knewtson et al 2012;Reeve and Drost 2012).…”
Section: Climate Changementioning
confidence: 99%
“…Driven by an interest in small-scale, local-market production systems and the cost share benefits provided by the NRCS EQIP HTI, high tunnel construction and use has increased significantly in the past 10 years (Bruce et al, 2017;Carey et al, 2009). Despite the benefits, high tunnel systems raise concerns about soil salinity (Knewtson et al, 2010), fertility management (Reeve and Drost, 2012), soilborne disease pressure (Kubota et al, 2008), and the need for increased irrigation inputs in the absence of rainfall (Lamont et al, 2003).…”
mentioning
confidence: 99%